Implementation of Customary Law in Settlement of Land Disputes in Indonesia - Riski, Naufal; Octaviyanda, Shafarra; Fernando, Wilson (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
Settlement of land disputes in Indonesia has become a complex and sensitive issue, considering the diversity of cultures, customs and laws that exist in this country. One approach that has been used to resolve land disputes is the implementation of customary law. This research aims to analyze how customary law is implemented in resolving land disputes in Indonesia. Before the Basic Agrarian Law (UUPA) was implemented in Indonesia, there were two land law systems in effect, namely western agrarian law and customary law. Western agrarian law includes concepts such as property rights, customary rights, and use rights. Land itself has a very important role in people's lives and livelihoods, especially in areas dominated by agriculture. Customary law varies greatly in that each law that regulates land rights will apply in that area. Even though there are differences from customary land, it is an important element in the formation of a state. The policy of unification of judicial bodies is one of the reasons why traditional courts are starting to be abandoned. UUKK itself also provides encouragement for the peaceful resolution of land disputes as part of the civil justice system. This research aims to provide insight into the implementation of customary law in resolving land disputes in Indonesia and understanding cultural and social dynamics in the context of dispute resolution. It is hoped that the results of this research can become a basis for formulating more effective policies in resolving land disputes involving customary law in Indonesia